2007
DOI: 10.1590/s0034-72992007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos índices de Helkimo e craniomandibular para diagnóstico de desordens temporomandibulares em pacientes com artrite reumatóide

Abstract: OBJETIVO: O estudo teve como finalidade avaliar a utilização de dois índices (Helkimo e craniomandibular) para o diagnóstico da desordem temporomandibular (DTM) em pacientes com Artrite Reumatóide (AR). MATERIAIS E MÉTODOS: A amostra foi de 80 pacientes divididos em dois grupos: pacientes com AR e pacientes sem AR. Em ambos os grupos os dois índices foram utilizados. No diagnóstico da DTM foram avaliados os seguintes sinais e sintomas: dor na ATM; limitação de abertura de boca e ruídos articulares. RESULTADOS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
(27 reference statements)
1
11
0
3
Order By: Relevance
“…Gomes et al (2012) investigated the effect of electrical stimulation with cathodic high voltage on pain only in women with TMD, since there are studies (Gonçalves et al, 2010) that refer that these were most affected by this pathology. da Cunha et al (2007) found no statistical difference in this variant (sex).…”
Section: Discussionmentioning
confidence: 75%
“…Gomes et al (2012) investigated the effect of electrical stimulation with cathodic high voltage on pain only in women with TMD, since there are studies (Gonçalves et al, 2010) that refer that these were most affected by this pathology. da Cunha et al (2007) found no statistical difference in this variant (sex).…”
Section: Discussionmentioning
confidence: 75%
“…A high workload, along with the fact that they spend many hours in the standing posture and/or with their necks flexed due tasks such as reading, preparing lessons and tests, and correcting homework and tests are some of the causes of neck pain among teachers. 3 4 5 6 7 8 9 10 11 12 13 14 …”
Section: Discussionmentioning
confidence: 99%
“…Although there are several and different questionnaires or indexes for the evaluation of cervical pain, including some of that have already been translated into Portuguese, such as the NDI and NPDS, these instruments only make the assessment in a subjective manner. 10 11 12 …”
Section: Introductionmentioning
confidence: 99%
“…Trata-se de um estudo do tipo epidemiológico, analítico, comparativo e quantitativo, cujos dados A utilização do índice permite uma quantificação confiável dos sinais e sintomas (13,14).…”
Section: Casuística E Metodologiaunclassified